Applications of Chiral Squaramides: From Asymmetric Organocatalysis to Biologically Active Compounds. Issue 2 (10th March 2016) - Han, Xin; Zhou, Hai‐Bing; Dong, Chune
Abstract: This review seeks to provide coverage on the recent advances in chiral squaramide‐catalyzed asymmetric transformations and their applications in the synthesis of a variety of chiral biologically active compounds. It aims to give an overview highlighting the new reaction types and enantioenriched medicinal scaffolds developed in the last few years. Abstract : This review seeks to provide coverage on the recent advances in chiral squaramide‐catalyzed asymmetric transformations and their application in the synthesis of a variety of chiral biologically active compounds. It aims to give an overview highlighting the new reaction types and enantioenriched medicinal scaffolds developed in the last few years.